Interprofessional Relations and the Emergence of a New Profession: Software Engineering in the United States, United Kingdom, and Canada. - Adams, Tracey L. (Sociological Quarterly)
This article explores the conditions under which interprofessional relations may be characterized by conflict and/or cooperation through a case study of the rise of a software engineering (SWE) profession in the United States, United Kingdom, and Canada. Analysis of professional journal publications produced by the primary computing organizations in all three countries reveals that the development of a SWE profession in the United Kingdom, and to a lesser extent, the United States, has been a collaborative project pursued by engineering and computing organizations. In contrast, the development of SWE in Canada has been characterized by intense interprofessional conflict. The investigation suggests that interprofessional conflict may be mitigated when professionalizing groups seeking to lay claim to the same jurisdiction are similar in terms of their organizational size, outlook, and regulatory status. Reprinted by permission of the publisher.